2010–2019 Florida Agricultural Deaths Summary: AE559/AE559, 05/2021 - Gorucu, Serap (EDIS, 2021)
This report summarizes fatal agricultural injury incidents in Florida between 2010 and 2019. This data is important for describing the size and characteristics of agricultural fatalities, populations at risk, risk factors, and temporal and spatial trends in injury rates. Written by Serap Gorucu, and published by the UF/IFAS Department of Agricultural and Biological Engineering, May 2021.